The Contribution of Self-Adjustment and Learning Skill to Qur’an Memorization Achievement of Boarding School Students - Renti Gusti Mulia; Neviyarni Neviyarni; Alizamar Alizamar (Universitas Negeri Padang, 2020)
Qur’an Memorization (Tahfiz Quran) score is a determinant factor of boarding students’ graduation. However, Many of the students get the score below the standard (KKM). Their ability to get high achievement could be caused by several factors such as their self-adjustment toward the learning environment and their learning skill. This study was conducted to reveal students’ self-adjustment, learning skill and achievement, and to perceive the contribution of aforementioned factors to students’ achievement. It was using correlation research method where the data was analysed through description and double regression. The research sample was 220 students consisted of students of grade seven and eight in Junior High School Ar-Risalah Padang. The result showed that self-adjustment and learning skill were in high category while student’s achievement was in moderate category. Then, there was a significantly positive contribution of the two factors on student’s learning achievement. In other words, the higher student’s self-adjustment and learning skill are the higher their learning achievement.